Dietary Modulation of Active Potassium Secretion in the Cortical Collecting Tubule of Adrenalectomized Rabbits - Wingo, Charles S. (1982)
Addisonian patients can maintain potassium homeostasis despite the absence of mineralocorticoid. The present in vitro microperfusion studies examine what role the cortical collecting tubule might play in this process. All studies were performed on tubules harvested from adrenalectomized rabbits, which were maintained on 0.15 M NaCl drinking water and dexamethasone 50 μg/d. Perfusion and bath solutions were symmetrical Ringer's bicarbonate with [K] of 5 meq/liter. Initial studies on cortical collecting tubules from adrenalectomized animals ingesting a high potassium chow (9 meq K/kg body wt) demonstrated net potassium secretion against an electrochemical gradient (mean collected fluid [K] 16.5±2.6 meq/liter with an observed transepithelial voltage of −6.3±4.1 mV; predicted voltage for passive distribution of potassium being −28.2 mV). To examine whether this active potassium secretion could be modulated by dietary potassium, independent of mineralocorticoid, two diets identical in all respects except for potassium content were formulated. Potassium secretion was compared in cortical collecting tubules harvested from adrenalectomized animals on low (0.1 meq K) and high (10 meq K) potassium intake. Mean net potassium secretion by cortical collecting tubules was 2.02±0.54 peq mm(−1) min(−1) in the low potassium diet group and 5.34±.74 peq·mm(−1)·min(−1) in the high potassium group. The mean transepithelial voltages of the collecting tubules did not differ between the two dietary groups. While net Na reabsorption was significantly greater in tubules from the high K group, this could not account for the differences in K secretion. These data demonstrate that: (a) the cortical collecting tubule can actively secrete potassium and that the magnitude of this potassium secretion correlates with potassium intake; (b) this active potassium secretory process in independent of mineralocorticoid. These findings support the hypothesis that the cortical collecting tubule may contribute to K homeostasis in Addison's disease.